EXPLORING POTENTIAL OF NOVEL HETEROCYCLIC COMPOUNDS AND THEIR STRUCTURE-ACTIVITY RELATIONSHIP IN PROSTATE CANCER TREATMENT - NAYAK, KAVANA KRISHNA; VERMA, RUCHI; KUMAR, LALIT (International Journal of Applied Pharmaceutics, 2025)
Prostate cancer is one of the leading causes of male death globally, and its overall incidence flaunts a rising trend over the years. Currently available treatment modalities for prostate cancer suffer from severe toxicity, unpredictable efficacy, high costs, and the emergence of resistance towards anti-cancer compounds. This substantiates the need to develop novel and potent anti-proliferative agents against prostate cancer. Multiple cellular mechanisms underlie the development of prostate cancer and, thus, multiple drug gable targets. In recent years, researchers have been conducting a myriad of investigations in this direction. This work recapitulates the synthesis of 78 such molecules based on recent references. These compounds are classified and tabulated according to the moiety that they possess. Further, the review study highlights the potent member of each chemical class. In addition, the review provides fundamental insights into the design and development of such compounds through the structure-activity relationship of each series of compounds, thereby unlocking new doors for future exploration.